1989
DOI: 10.1210/jcem-69-6-1291
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Forms of Serum Insulin-Like Growth Factor (IGF)-Binding Proteins in Man: Relationships with Growth Hormone and IGFs and Physiological Significance*

Abstract: Insulin-like growth factor-I (IGF-I) and IGF-II are associated in the blood with specific binding proteins (BPs), forming complexes that elute in gel filtration with estimated mol wt around 40 and 150 kD. The latter appears to be under GH control. Five molecular forms of BP (41.5, 38.5, 34, 30, and 24 kD) have been identified by Western blotting using 125I-labeled IGF. All five forms are present in the smaller complexes, but only the 41.5- and 38.5-kD forms are found in the larger complexes. In this study immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
81
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 200 publications
(98 citation statements)
references
References 41 publications
15
81
0
2
Order By: Relevance
“…In contrast to insulin and IGF-I, a response to GH was not observed. In view of altered IGFBP serum concentrations in states of GH excess or deficiency reported previously, 33,34 this latter observation supports the concept that GH acts indirectly on hepatic IGFBP biosynthesis, e.g., by increasing levels of insulin or IGF-I. A similar mechanism of GH regulatory action has been suggested by Camacho-Hubner et al, 35 demonstrating increased IGFBP-3 serum levels in GH-deficient mice overexpressing a transgene for IGF-I.…”
Section: P0c$$0024supporting
confidence: 77%
“…In contrast to insulin and IGF-I, a response to GH was not observed. In view of altered IGFBP serum concentrations in states of GH excess or deficiency reported previously, 33,34 this latter observation supports the concept that GH acts indirectly on hepatic IGFBP biosynthesis, e.g., by increasing levels of insulin or IGF-I. A similar mechanism of GH regulatory action has been suggested by Camacho-Hubner et al, 35 demonstrating increased IGFBP-3 serum levels in GH-deficient mice overexpressing a transgene for IGF-I.…”
Section: P0c$$0024supporting
confidence: 77%
“…23,24 According to endocrinological assays, pygmy individuals have normal levels of GH but lower serum levels of IGF1, and exhibit an eightfold underexpression of the GHR gene as compared with the controls. 16,18,19 Therefore, the GHR and IGF1 genes represent good candidates to explain pygmies' short stature. We develop here a candidate-gene approach focusing on these two genes and on the signal transducers and activators of transcription STAT5A and STAT5B.…”
Section: Study Design and Choice Of The Candidate Genesmentioning
confidence: 99%
“…18 Small regions of the GHR and IGF1 genes have been previously tested for association with the stature of African pygmies with negative results. [18][19][20][21] A recent genome-wide study has identified regions in the genome that might be involved in the difference in stature observed between pygmies from Cameroon and their non-pygmy neighbors, although this signal was not significant. 22 Some of these regions contain genes linked to the GH-IGF1 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In general, each cell type secretes a distinct pattern of binding proteins and changes in their secretion are associated with changes in certain cell functions. In various pathologic states, the level of one or more of these IGFBP has been found to disrupt the normal metabolism through sequestration of the IGF (34,35).…”
Section: This Study Extends Our Previous Observations (S)mentioning
confidence: 99%
“…For example, in human fibroblasts, both IGF-1 and transforming growth factor p demonstrated their ability to increase levels of IGFBP-3 and 4, and in the case of IGF-1, without influencing the transcript levels (35,543). In certain cell types, the intracellular level of CAMP also seemed to increase both the protein and the mRNA expressions of IGFBP-4 (42,56).…”
mentioning
confidence: 99%